Utilização de probiótico biorremediador na água do cultivo de tilápia do Nilo - Feitosa, Vinícius Alcoforado Vieira (2018)
This study was carried out to evaluate the effects on water quality, productive performance and histology hepatic and gut tissues of Nile tilapia submitted to weekly application of bioremediation composed of a mix of Bacillus spp. and Lactococcus lactis ssp. Ninety fingerlings of Oreochromis niloticus were used, with a mean initial weight of 3.67 ± 0.56 g, distributed in a static system and cultivated for 75 days. The bioremediator was applied weekly at increasing doses (0.00, 0.02, 0.04, 0.06 and 0.08 g) directly in the water of experimental units of 60 L. The data of water quality and gut histomorphometry were submitted to principal component analysis (PCA) and analyzes of repeated measures ANOVA MR and unidirectional ANOVA, respectively. The performance and histological variables of fish liver were submitted to One-way ANOVA, following test of Tukey at 5% significance level. Concentrations of nitrate, nitrite, total nitrogen, biochemical oxygen demand and chemical oxygen demand increased over time due to the culture system. Considering the PCA evaluation, it was verified that the water quality variables did not present statistical differences, as well as, there was no effect of interaction time x dose applied (p>0.05). The different doses of the bioremediator did not influence the productive performance of the fish. The number of hepatocytes in the fish submitted to the application of 0.08 g of bioremediator was lower in relation to the control (p<0.05). The height, length, thickness and width of villi and the thickness of intestinal tunica in the fish submitted to 0.06 g of bioremediator were higher (p<0.05) in relation to the other doses evaluated. Therefore, the application of different bioremediator doses does not interfere efficiently in the system with continuous deficit in water quality, although it influences the development of fish.